Outcome of pregnancies with Covid-19 at Prof. Dr. R. D. Kandou Hospital Manado from March 2020 to August 2021 - Adelina M. Lintang; Freddy W. Wagey; Suzanna P. Mongan (e-CliniC, 2022)
Abstract: COVID-19 is spreading very quickly worldwide with a high mortality rate. Pregnant women are a vulnerable population exposed to COVID-19. There was an increase in pregnant women's deaths about 10-fold during this pandemic. This study aimed to obtain the outcome of pregnancy with COVID-19 at Prof. Dr. R. D. Kandou Manado Hospital from March 2020 to August 2021. This was a descriptive and retrospective study with a cross sectional design. The results showed 53 pregnant women confirmed with COVID-19 and 55 babies were born with two twin births. Pregnant women confirmed COVID-19 were dominated at the age of 20-35 years (66%), symptomatic fever (38%), alive (91%), and had caesarea section (70%). Babies were predominantly fullterm (84%), alive (89%), normal body weight (71%), moderate APGAR score (AS) 1 (47%), and good AS 5 (76%). In conclusion, the outcome of pregnancy with COVID-19 is relatively good.Keywords: pregnancy outcome; COVID-19Â Abstrak: COVID-19 menyebar sangat cepat secara luas dengan angka mortalitas yang tinggi. Ibu hamil merupakan populasi rentan terpapar COVID-19. Terjadi peningkatan kematian ibu hamil sekitar 10 kali lipat selama pandemi ini. Penelitian ini bertujuan untuk mengetahui luaran kehamilan dengan COVID-19 di RSUP Prof. Dr. R. D. Kandou Manado periode Maret 2020â€“Agustus 2021. Jenis penelitian ialah deskriptif retrospektif dengan desain potong lintang. Hasil penelitian mendapatkan 53 ibu hamil terkonfirmasi COVID-19 dan 55 bayi lahir dengan dua kelahiran kembar. Ibu hamil terkonfirmasi COVID-19 didominasi pada usia 20-35 tahun (66%), bergejala demam (38%), kondisi hidup (91%), dan persalinan sectio caesarea (70%). Bayi yang lahir didominasi pada usia cukup bulan (84%), lahir hidup (89%), BBL normal (71%) dan APGAR score (AS) 1 sedang (47%), AS 5 baik (76%). Simpulan penelitian ini ialah luaran kehamilan dengan COVID-19 relatif baik.Kata kunci: luaran kehamilan; COVID-19